1977
DOI: 10.1515/zna-1977-3-419
|View full text |Cite
|
Sign up to set email alerts
|

On the Thermal Behaviour of Long-chain Potassium n.alkanoates

Abstract: Differential scanning calorimetry was performed between 110 K and the isotropic melt region on potassium «.alka noates from octanoate to dodecanoate. Clearing, melting and (crystalline) solid state transition temperatures and heat effects were measured. In the higher homologues the occur rence of phases (likely "waxy") intermediate between crys talline solid and mesomorphic liquid could also be argued. The phase relationships are discussed in comparison with some roentgenographic and microscopic results of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
15
0

Year Published

1980
1980
2005
2005

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 0 publications
5
15
0
Order By: Relevance
“…In the case of potassium caprate, the first phase transition occurred at 75.5 °C where ∆H ) 1.96 kcal/mol and ∆S ) 5.62 cal/(K mol). 7 The second phase transition occurred at 109.7 °C where ∆H ) 0.24 kcal/mol and ∆S ) 0.63 cal/(K mol). These ∆H and ∆S are sufficiently smaller than those of decane and decanoic acid, indicating the partial melting of the chain occurred at these transitions.…”
Section: B Structural Transition Behaviormentioning
confidence: 98%
See 1 more Smart Citation
“…In the case of potassium caprate, the first phase transition occurred at 75.5 °C where ∆H ) 1.96 kcal/mol and ∆S ) 5.62 cal/(K mol). 7 The second phase transition occurred at 109.7 °C where ∆H ) 0.24 kcal/mol and ∆S ) 0.63 cal/(K mol). These ∆H and ∆S are sufficiently smaller than those of decane and decanoic acid, indicating the partial melting of the chain occurred at these transitions.…”
Section: B Structural Transition Behaviormentioning
confidence: 98%
“…Besides these studies, Feloni et al reported reliable thermal data on these transitions using high-purity specimens over 99%. [7][8][9][10] The phase transitions occur at 75.5 °C and 109.7°, and 271 °C from crystalline phase to lamellar liquid crystalline phase and at 423 °C to isotropic liquid. There have also been several studies concerning these transitions.…”
Section: Introductionmentioning
confidence: 99%
“…The compounds with an odd number of carbon atoms have been investigated in much less detail. An Italian groups of researchers investigated lithium, 275 sodium, 275 potassium, 276 rubidium, 277 and cesium 278 soaps with an odd number of carbon atoms by DSC. There is in the literature some dispute about the phase behavior of the lithium alkanoates.…”
Section: Alkali Metal Alkanoatesmentioning
confidence: 99%
“…Let us consider as an example the case of KC10, for which previous DSC [3] and It can be observed that the clearing peak is sharper and occurs at a somewhat higher temperature in the DSC than in the DTA record. This is a common feature of the whole homologous series KC5 ..... KC12 (the above difference in temperature amounting on average to = 7 K), and is reasonably justifiable as follows: (i) all of the salts concerned are characterized by a more or less marked hygroscopicity; (ii) the operational procedure adopted in the case of DSC allowed measurements on samples which had not been exposed to atmospheric moisture; (iii) for instrumental reasons, contact with the atmosphere could not be avoided Anal.…”
mentioning
confidence: 99%
“…In an oxygen atmosphere decomposition starts simultaneously with fusion in the case of the lower homologues, but even at a somewhat lower temperature (falling within the plastic region, see Fig. 1) in the case of the higher ones: the DTG curves prove that the (exothermic) process occurs through a succession of steps and becomes increasingly complicated as n c increases (nc Table 1 Clearing, fusion and decomposition temperatures, K DSC [2,3] is the number of carbon atoms). In nitrogen, in contrast, the stability range extends up to Clearing temperatures or even, a few degrees higher, while decomposition proceeds endothermically, giving rise with all homologues to a single, almost symmetrical DTG peak.…”
mentioning
confidence: 99%